Convection Driven Ultrarapid Protein Detection via Nanobody‐Functionalized Organic Electrochemical Transistors. Issue 35 (28th July 2022) - Koklu, Anil; Wustoni, Shofarul; Guo, Keying; Silva, Raphaela; Salvigni, Luca; Hama, Adel; Diaz‐Galicia, Escarlet; Moser, Maximilian; Marks, Adam; McCulloch, Iain; Grünberg, Raik; Arold, Stefan T.; et al.
Abstract: Conventional biosensors rely on the diffusion‐dominated transport of the target analyte to the sensor surface. Consequently, they require an incubation step that may take several hours to allow for the capture of analyte molecules by sensor biorecognition sites. This incubation step is a primary cause of long sample‐to‐result times. Here, alternating current electrothermal flow (ACET) is integrated in an organic electrochemical transistor (OECT)‐based sensor to accelerate the device operation. ACET is applied to the gate electrode functionalized with nanobody–SpyCatcher fusion proteins. Using the SARS‐CoV‐2 spike protein in human saliva as an example target, it is shown that ACET enables protein recognition within only 2 min of sample exposure, supporting its use in clinical practice. The ACET integrated sensor exhibits better selectivity, higher sensitivity, and lower limit of detection than the equivalent sensor with diffusion‐dominated operation. The performance of ACET integrated sensors is compared with two types of organic semiconductors in the channel and grounds for device‐to‐device variations are investigated. The results provide guidelines for the channel material choice in OECT‐based biochemical sensors, and demonstrate that ACET integration substantially decreases the detection speed while increasing the sensitivity and selectivity of transistor‐based sensors. Abstract : Introducing alternating current electrothermal flow (ACET) at the sample incubation step accelerates the operation of an organic‐electrochemical‐transistor‐based protein sensor with a limit of detection at the attomolar range. The ACET integrated sensor exhibits a sample‐to‐result time of 2 min, with better selectivity, higher sensitivity, and lower limit of detection than the equivalent sensor with diffusion‐dominated operation.